The process of adapting to mobile tablet devices by switching between distractive and productive multitasking - Park, Sora (AoIR Selected Papers of Internet Research, 2013)
This study explores how new users of mobile devices experience and learn to adapt to the distraction they encounter due to the ubiquitous nature of the devices. After giving young adults mobile tablet devices, this study tracked the changes in uses over the course of one year. A mixed method of online surveys and netnography were conducted on 35 participants in Australia. Participants engaged in continuous access throughout the day, expanding situations of where they engage in multiple tasks. They reported both distraction and productivity gains. During the course of the study, participants negotiated their time and attention that they gave to their devices switching from productive to distractive multitasking. The concept of self regulation emerged from the process of managing the distraction, the main strategies being preventive and pre-emptive use.